2018
DOI: 10.3233/jad-170996
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Cognitive Function are Positively Related Among Participants with Mild and Subjective Cognitive Impairment

Abstract: These findings suggest that during the earliest stages of cognitive impairment PA and exercise capacity might present a marker for the risk of further cognitive decline. This finding warrants further investigation using longitudinal cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 67 publications
2
20
0
1
Order By: Relevance
“…All participants were recruited through the NeuroExercise Project [13,14], a multi-centered randomized controlled trial of exercise therapy in persons with MCI according to Albert et al [15] across three European countries [13]. For the purpose of the present sub-study, the participants were recruited in Germany at the German Sport University (GSU).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants were recruited through the NeuroExercise Project [13,14], a multi-centered randomized controlled trial of exercise therapy in persons with MCI according to Albert et al [15] across three European countries [13]. For the purpose of the present sub-study, the participants were recruited in Germany at the German Sport University (GSU).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Participants were included if the Montreal Cognitive Assessment (MoCA) [16] scored ranged between 18 and 26; if they had a stable medical condition for more than 6 months and stable medication for more than 3 months; adequate visual and auditory acuity to complete neuropsychological testing, electrocardiogram without significant abnormalities that might interfere with the study; physical ability sufficient to allow performance of endurance exercise training; capacity to provide written and dated informed consent form, as well as having complete physical examination including a symptom-limited cardiopulmonary exercise test. To distinguish between amnestic and non-amnestic MCI, agreed education adjusted cut-offs of −2 Standard Deviation (SD) for low education (<10 years of education), −1.5 SD for the middle group (10–13 years of education), and −1 SD for the highly educated (>13 years of education) were derived from the delayed recall portion of the age-adjusted delayed memory index of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) [17] (Score of < 85) as previously described [13,14].…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anhand von vorherigen Studien kann gemutmaßt werden, dass stärker Betroffene sozial zurückgezogener leben und eine geringere körperliche Fitness besitzen als weniger stark erkrankte Personen [35,36]. Da sowohl die soziale Interaktion als auch die körperliche Fitness durch ein angeleitetes Sporttraining gefördert werden, ist es denkbar, dass besonders stärker Betroffene von einem gezielten Sporttraining profitieren können.…”
Section: Diskussionunclassified
“…Large population studies have found that, along with hearing loss, inactivity and low levels of physical fitness are the predominant modifiable lifestyle factors associated with increased rates of dementia, exceeding other primary areas of focus such as obesity, diabetes, hypertension, and smoking [21,22]. In an older cohort, individuals with the most cognitive impairment were found to have the lowest levels of cardio-respiratory fitness and least engagement in physical activity [23]. A meta-analysis of MRI studies also concluded that, although the effect sizes were small, lower levels of physical fitness and activity are associated with lower white matter volume, and increased white matter lesion volume and severity [24].…”
Section: Introductionmentioning
confidence: 99%